Occurrence of dapple fruit of plum in Italy - Ragozzino, E.; Faggioli, F.; Amatruda, G.; Barba, M. (Phytopathologia Mediterranea, 2002)
In the course of a field survey of viroids of stone fruit trees in southern Italy, we encountered someparticular fruit symptoms in plum cv. Florentia and Sorriso di Primavera, which resembled the symptoms of a diseasedescribed in Japan in 1989 and was named dapple fruit disease. Symptoms consisted mainly of discolored spotson the fruit skins, and led to loss of market value. Hop stunt viroid (HSVd) was found in all symptomatic trees, butnot in any symptomless samples. No other viroid was found in these trees. All samples were also checked for the morecommon viruses affecting plum. Apple chlorotic leaf spot trichovirus (ACLSV) was detected in both symptomatic andsymptomless trees in similar percentages but no other viruses were found in any of the samples. These resultsprovide evidence for the belief that HSVd is the cause of dapple fruit. This is the first report of dapple fruit in Italy.